FROM THE EXPERIENCE OF USING STRATEGIES FOR DEVELOPING READING SKILL - Eshniyazova, T. (FAN va JAMIYAT, 2019)
The article deals with the issues of developing reading skills of language learners in English learning classrooms. The author shares her experience of working with jigsaw reading strategy and evaluates its effectiveness in giving learners opportunity to read texts more attentively, in developing learners’ responsibility for their knowledge.